Review of Urbanization Models and its Implication to Reduce Urban Poverty - Teguh Widodo; Indang Dewata (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Urbanization in nature has two meanings. Firstly, it means migrating people from rural to urban. Second, it means transforming rural area to urban area. Those meanings have two implications for the population as well. The people who migrate from rural to the urban area tend to make the change voluntarily. They want to change their life better than when they lived in rural. On the other hand, the villagers forced by the situation being too urban tend to be apathetic and they are very difficult to adapt and to change so that they are finally forced to change. This paper aims to explain how urbanization happened in Indonesia and its implication on urban poverty. This study depends on investigating literature and media review. We argue that voluntarily urbanization may lead to the new formation of the urban periphery. This will bring economic and social consequences such as land acquisition, job opportunity and urban poverty. Further, the study indicated that under voluntary urbanization, social and economic pressure were more likely to attach to the indigenous community compared to forced urbanization. The study showed that programs on poverty alleviation need to consider the nature of urbanization. Finally, this paper suggests conducting an empirical study related to urban poverty caused by two types of urbanization.